Determinants of Discharge Planning Implementation - Ellis Siti Suhartini; Harif Fadhillah; Eni Widiastuti; Muhammad Hadi (GLOBAL HEALTH SCIENCE GROUP, 2026)
Discharge planning a day prior to discharge is vital for care continuity. TThis study aims to analyze the determinants of nursing service quality, including nurse competence, knowledge, motivation, and role perception. A descriptive correlational study with a cross-sectional design was conducted involving 110 associate nurses in the inpatient ward using a total sampling technique. Data were collected using structured questionnaires and observation checklists. Prior to data collection, the instruments were tested for validity and reliability. The validity test results indicated that all questionnaire items were valid, while the reliability test showed good internal consistency with Cronbach’s alpha values greater than 0.70 for each variable. Data were analyzed using multiple linear regression to determine the influence of nurse competence, knowledge, motivation, and role perception on the quality of nursing services.. The observation results showed a very high compliance rate (90.9 percent). The analysis proved that competence, knowledge, and nurse roles were not significant. Nurse motivation was proven to be the only dominant factor influencing the compliance level. In conclusion, intrinsic motivation determines nurse performance amidst competence and procedural homogeneity.